XynDZ5: A New Thermostable GH10 Xylanase - Zarafeta, Dimitra; Galanopoulou, Anastasia P.; Leni, Maria Evangelia; Kaili, Stavroula I.; Chegkazi, Magda S.; Chrysina, Evangelia D.; Kolisis, Fragiskos N.; Hatzinikolaou, Dimitris G.; Skretas, Georgios (Frontiers in Microbiology, 2020)
Xylanolytic enzymes have a broad range of applications in industrial biotechnology as biocatalytic components of various processes and products, such as food additives, bakery products, coffee extraction, agricultural silage and functional foods. An increasing market demand has driven the growing interest for the discovery of xylanases with specific industrially relevant characteristics, such as stability at elevated temperatures and in the presence other denaturing factors, which will facilitate their incorporation into industrial processes. In this work, we report the discovery and biochemical characterization of a new thermostable GH10 xylanase, termed XynDZ5, exhibiting only 26% amino acid sequence identity to the closest characterized xylanolytic enzyme. This new enzyme was discovered in an Icelandic hot spring enrichment culture of a Thermoanaerobacterium species using a recently developed bioinformatic analysis platform. XynDZ5 was produced recombinantly in Escherichia coli, purified and characterized biochemically. This analysis revealed that it acts as an endo-1,4-β-xylanase that performs optimally at 65-75 oC and pH 7.5. The enzyme is capable of retaining high levels of catalytic efficiency after several hours of incubation at high temperatures, as well as in the presence of significant concentrations of a range of metal ions and denaturing agents. Interestingly, the XynDZ5 biochemical profile was found to be atypical, as it also exhibits significant exo-activity. Computational modelling of its three-dimensional structure predicted a (β/α)8 TIM barrel fold, which is very frequently encountered among family GH10 enzymes. This modelled structure has provided clues about structural features that may explain aspects of its catalytic performance. Our results suggest that XynDZ5 represents a promising new candidate biocatalyst appropriate for several high-temperature biotechnological applications in the pulp, paper, baking, animal-feed and biofuel industries.